Examining Peacebuilding Strategies Amid Socio-Religious Conflicts: The Case of Pesantren Waria in Yogyakarta - Salsabila, Astrid Syifa (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2024)
The establishment of Pesantren Waria in Yogyakarta has faced various challenges, reflecting broader tensions between religious conservatism and the rights of transgender individuals in Indonesia. Since its founding, the pesantren has provided a safe space for waria (trans women) to practice their faith. However, it has encountered significant opposition, including its forced closure by the Front Jihad Islam (FJI) in 2016. This study aims to examine the conflict between Pesantren Waria and FJI and to identify appropriate peacebuilding interventions. The research focuses on understanding the socio-economic and religious dimensions of the conflict and how these factors have contributed to its escalation. This study employs a qualitative approach, including a literature review, interviews, and the use of Johan Galtung's ABC Triangle of Conflict and Lisa Schirch's peacebuilding model. The findings reveal that the conflict was driven not only by religious factors but also by socio-economic motivations, particularly FJI's desire to control local resources. While religious interpretation played a role, the conflict extended beyond theological debates. The study highlights the importance of involving local authorities, particularly the Yogyakarta Palace, in fostering sustainable peace. Effective interventions must consider the interests of all parties and the local context, rather than focusing solely on religious reconciliation. Pendirian Pesantren Waria di Yogyakarta menghadapi berbagai tantangan, hal ini mencerminkan ketegangan yang lebih luas antara konservatisme agama dan hak-hak individu transgender di Indonesia. Sejak awal pendiriannya, pesantren ini menyediakan ruang aman bagi waria (trans perempuan) untuk beribadah. Namun mendapat perlawanan signifikan, termasuk penutupannya secara pak sa oleh FJI (Front Jihad Islam) pada tahun 2016. Penelitian ini bertujuan untuk mengkaji konflik antara Pesantren Waria dan FJI serta menemukan intervensi perdamaian yang tepat. Fokus penelitian adalah memahami dimensi sosial-ekonomi dan agama dari konflik tersebut serta bagaimana faktor-faktor ini mempengaruhi eskalasinya. Penelitian ini menggunakan pendekatan kualitatif berupa tinjauan literatur, interview, serta menggunakan kerangka analisis konflik Segitiga ABC Johan Galtung dan model perdamaian Lisa Schirch. Hasil penelitian menunjukkan bahwa konflik ini dipicu tidak hanya oleh alasan agama, tetapi juga faktor sosial-ekonomi, terutama keinginan FJI untuk mengendalikan sumber daya lokal. Sementara interpretasi agama berperan, konflik ini melampaui perdebatan teologis. Studi ini menekankan pentingnya keterlibatan otoritas lokal, khususnya Keraton Yogyakarta, dalam menciptakan perdamaian yang berkelanjutan. Intervensi yang tepat harus mempertimbangkan kepentingan semua pihak dan konteks lokal, bukan hanya berfokus pada rekonsiliasi agama.